Central European polyploids of Sorbus subgenus Aria (Rosaceae) recurrently evolved from diploids of central and south-eastern Europe: evidence from microsatellite data. (1st October 2019) - Feulner, Martin; Weig, Alfons; Voss, Tobias; Schott, Lea F; Aas, Gregor
Abstract: Sorbus subgenus Aria in Europe consists of sexual diploid and predominantly apomictic polyploid taxa. Tetraploid taxa of Sorbus subgenus Aria, including S. danubialis and S. collina, are endemic to central Europe, but it is unclear from which taxa or populations they originated. South-eastern European taxa of subgenus Aria were suggested to have contributed to the tetraploids S. danubialis and S. collina by polyploidization or hybridization. Genetic microsatellite data, flow cytometry and multivariate morphometrics were used (1) to investigate the genetic relationship of the tetraploid taxa throughout Europe, (2) to disentangle the population structure of diploid S. aria from central and south-eastern Europe and (3) to use the resulting subgroups for estimating the parentage of polyploids. Parentage analyses revealed that the allele patterns of the polyploid central European taxa such as S. danubialis and S. collina and other as yet undescribed polyploids from south-western Germany could be explained in most cases by recurrent crosses between diploid S. aria from south-eastern and central Europe. These origins are discussed in the context of historical biogeography. Furthermore, we report the exceptional case of a polyploid subgenus Aria population from south-western Germany showing no clonal genetic structure at all, making its taxonomic treatment challenging.